Modified Roux-en-Y gastric bypass surgery avoids complications in mice - Dan Tong; Jie Xiang; Peng Gao; Zhiming Zhu; Zongshi Lu (PLoS ONE, 2025)
Background Roux-en-Y gastric bypass（RYGB）surgery delivers an improvement in obesity and obesity-related risks. However, due to the limited operational space in the abdominal cavity of mice, the technical complexity of RYGB surgery and the postoperative complications hinder its mechanism research. The aim was to develop a device that makes it easier to anastomose the esophagus to the jejunum. Methods We have invented a simple gastrointestinal anastomosis auxiliary device consisting of a rigid front end and a flexible rear end. Thirty male C57BL6J mice were subjected to RYGB with an auxiliary device. Postoperative recovery and survival status of mice were evaluated using body weight, food intake, body fat, and glucose tolerance. Results Based on the RYGB surgical methodology reported in previous literature, the anastomosis device described in this article assists in end-to-end anastomosis of the esophagus and jejunum, which reduces surgical difficulty and time. CT scan results revealed that, following a short - term recovery period after mRYGB surgery, no leakage or stenosis was detected at the anastomotic site in the mice. Moreover, after postoperative recovery, there was no significant difference in food intake, weight and body fat distribution compared with Sham mice, but the glucose tolerance of mRYGB mice was significantly improved. Conclusions Our modified RYGB surgical method can effectively avoid the problems of anastomotic leakage and stenosis in mice and improve long-term quality of life.